AN ECLECTIC APPROACH IN SYLLABUS DESIGN: A PRELIMINARY STUDY OF ONE-TO-ONE TEACHING INDONESIAN FOR SPEAKERS OF OTHER LANGUAGES - Sundari, Hanna; Miranti, Ira; Sulaeman, Agus (Jurnal Pendidikan Bahasa dan Sastra, 2020)
The industry of BIPA (Indonesian for foreigners) has extensively increased both at home and overseas. As a result, its teaching needs to be well-planned and organized. Supported by the view that no best method for all, eclecticism can be selected as approach to teaching. This paper is purposed to describe the initial stages of syllabus design particularly for one-to-one teaching Indonesian using eclectic approach. Carried out by descriptive research as part of research and development design, non-structured interview, observation, and open-ended questionnaire were as instruments to collect the information about learner and previous teaching process. Using a framework of syllabus development by Graves, need analysis and first draft syllabus were taken place. The need analysis reveals the learner characteristics and need of learning, such as age, gender, motivation and expectation. Moreover, grounded by the result of gathered information from need analysis, the developed syllabus is then a combination of task-based approach of language learning and structural-based syllabus which embraces accuracy and fluency as well as covers the features of eclectic system.Â